Osmotic regulation of Rab-mediated organelle docking - Brett, Christopher L. (2008)
Osmotic gradients across organelle and plasma membranes modulate the rates of membrane fission and fusion; sufficiently large gradients can cause membrane rupture [1–6]. Hypotonic gradients applied to living yeast cells trigger prompt (within seconds) swelling and fusion of Saccharomyces cerevisiae vacuoles, while hypertonic gradients cause vacuoles to fragment on a slower time scale [7–11]. Here, we analyze the influence of osmotic strength on homotypic fusion of isolated yeast vacuoles. Consistent with previously reported in vivo results, we find that decreases in osmolyte concentration increase the rate and extent of vacuole fusion in vitro, while increases in osmolyte concentration prevent fusion. Unexpectedly, our results reveal that osmolytes regulate fusion by inhibiting early, Rab-dependent docking or predocking events, not late events. Our experiments reveal an organelle-autonomous pathway that may control organelle surface to volume ratio, size and copy number: decreasing the osmolyte concentration in the cytoplasmic compartment accelerates Rab-mediated docking and fusion. Fusion, by altering the organelle surface-to-enclosed volume relationship, in turn reduces the risk of membrane rupture.